Low-band gap copolymers based on diketopyrrolopyrrole and dibenzosilole and their application in organic photovoltaics. (November 2017) - Ha, Yeon Hee; Hong, Jisu; An, Tae Kyu; Yun, Hui-Jun; Kim, Kyunghun; Park, Chan Eon; Kim, Yun-Hi; Kwon, Soon-Ki
Abstract: We report donor-acceptor copolymers incorporating electron-donating dimethylsilole and electron-withdrawing diketopyrrolopyrrole (DPP) units. To investigate effects of alkyl chain attached to the DPP unit, 2-decyltetradecyl (24-alkyl) group and 7-decylnonadecyl (29-alkyl) with linear space group were introduced to DPP units. Two polymers, P24DPP-Silole and P29DPP-Silole, exhibited low band gap of 1.46 and 1.36 eV, respectively, and low-lying lowest unoccupied molecular orbital (LUMO) energy level of −3.85 eV. Photovoltaic devices employing P24DPP-Silole and P29DPP-Silole exhibited the highest power conversion efficiencies of 4.17% and 4.33%, respectively, with 1-chloronaphthalene (CN) as a processing additive. Morphological analyses were conducted with atomic force microscopy (AFM), transmission electron microscopy (TEM), and grazing incidence wide-angle x-ray scattering (GIWAXS) to investigate the effects of different alkyl chain on DPP units and processing additive. The analyses revealed that the addition of CN led to favorable phase separation and increased the degree of crystallinity in blend films. This study demonstrates that the copolymerization of DPP and dibenzosilole units is an effective means of narrowing the optical band gap. Furthermore, the length of alkyl chains on DPP units did not significantly affect on the photovoltaic performances and bulk heterojunction morphologies. Highlights: Low-band gap copolymers based on diketopyrrolopyrrole and dibenzosilole. Investigate on the effects of alkyl chain attached to P24DPP-Silole and P29DPP-Silole for photovoltaic performance. The power conversion efficiencies of P24DPP-Silole and P29DPP-Silole with CN additive exhibited 4.17% and 4.33%.